Deformation Mechanisms in Compositionally Complex Polycrystalline CoNi-Base Superalloys: Influence of Temperature, Strain-Rate and Chemistry - Bezold, Alexander; Freund, Lisa; Förner, Andreas; Völkl, Johannes; Huber, Laura-Kristin; Göken, Mathias; Neumeier, Steffen (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
Recent studies revealed the excellent high temperature properties of polycrystalline CoNi-base superalloys. However, their underlying deformation behavior has been reported only scarcely so far. In this work, the deformation mechanisms of four polycrystalline compositionally complex CoNi-base superalloys with slightly varying chemical compositions were investigated by compression and creep experiments at temperatures between 750 degrees C and 850 degrees C and strain-rates between 10 (3) and 10 (8) s(-1). In the two (Ta + Ti)-rich alloys, a transition of the deformation mechanism from shearing by APB-coupled dislocation pairs to stacking fault shearing and finally also to microtwinning is observed with decreasing strain-rate and increasing temperature. In contrast, APB-based shearing mechanisms represent the dominant mechanism in both (Al + W)-rich alloys in all conditions. At high temperatures and low strain-rates, dislocation glide-climb processes also contribute to plastic deformation in all alloys. By correlating the underlying defect structures with the mechanical properties of these alloys, it becomes evident that a transition to stacking fault shearing and microtwinning leads to a lower strain-rate dependency and superior high-temperature strength in comparison with APB-based mechanisms. Reasons for the different deformation mechanisms, the influence of segregation processes, the consequences for mechanical properties and implications for a mechanism-based alloy design are discussed.
CRIS-Team WoS Importer:2023-01-06